The Influence of Youtube Content on Nationalism in The Millennial Generation at Jenderal Soedirman University - Didik Suwarno; Abdul Basit (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Nationalism which is a natural love for the homeland that provides awareness to the community which will then provide an impetus to uphold sovereignty, make the country in accordance with the approved nationality and willing to sacrifice for the benefit of the nation and state. The research method uses qualitative methods and descriptive approaches with informant sources of Jenderal Sudirman University students. The effect of YouTube content on nationalism may vary depending on the type of content consumed by users. Enhanced Historical and Cultural Understanding: YouTube provides easy access to historical, cultural, and traditional videos from different countries. By watching such content, users can increase their understanding of the history and culture of their own country. The influence of YouTube's internal and external factors in shaping nationalism can play a significant role in a person's understanding and perception of the country and national identity. YouTube's influence on nationalism in the teenage generation is significant. This platform has the potential to strengthen a sense of love and pride for the country, while shaping teenagers' perceptions and understandings of nationalism. Through diverse content, YouTube can influence the way teenagers see and interpret nationalism. YouTube can make a positive impact by providing easy access to information about national history, culture, and achievements.